Iron-activated carbon nanocomposite: synthesis, characterization and application for lead removal from aqueous solution. Issue 49 (3rd May 2016) - Sharififard, H.; Pepe, F.; Soleimani, M.; Aprea, P.; Caputo, D.
Abstract : An iron-activated carbon nanocomposite synthesized by a facile, low temperature technique was successfully tested for Pb(ii ) removal from aqueous solutions. Abstract : The removal of Pb(ii ) ions from aqueous solution by adsorption on an Iron-Activated Carbon (IAC) nanocomposite was investigated. Removal studies were carried out in a batch system, and the effects of various operating parameters, such as solution pH, solid to liquid ratio and initial concentration were evaluated. Experimental design was carried out using central composite design (CCD) with response surface methodology (RSM). According to the RSM results, the optimum adsorption conditions for Pb(ii ) removal by IAC were pH = 6.5, solid to liquid ratio of 3 g L −1 and initial lead concentration of 10 mg L −1 . Under these optimum operating conditions, 96.5% of Pb(ii ) was removed by the IAC nanocomposite. The equilibrium adsorption data were well described by the Freundlich isotherm. The maximum adsorption capacity of IAC was 121.9 mg g −1 for Pb(ii ). It was observed that the adsorption kinetics of Pb(ii ) on the IAC could be well analyzed with a pseudo-second-order model.